Edukasi Tablet Tambah Darah bagi Remaja Putri untuk Pencegahan Stunting di SMPN 2 Ciledug - Aini, Mayang Nur; Abdurrahman, Naufal Hafiz; Safira AS, Zahra; Rajuwi, Seftianti; Lutfiani, Rizka; Riantika, Herpina; Noris, Putri Syahrani Roma; Firza, Ahmad; Nasution, Zuraidah (Jurnal Pusat Inovasi Masyarakat, 2024)
Anemia is a condition of hemoglobin levels below normal limits which has the potential to increase the risk of stunting in future pregnancies of adolescent girls. Stunting is a health problem that is influenced by the nutritional status of the mother during pregnancy. To prevent stunting, early intervention through the provision of Blood Additive Tablets (TTD) in adolescent girls is crucial. The educational activity entitled “Healthy Teenagers, Great Indonesia” was held at SMPN 2 Ciledug, Jatiseeng Kidul Village, Ciledug Village, Cirebon Regency. This program aims to improve the knowledge and attitude of adolescents regarding TTD consumption to prevent stunting. Education was carried out through powerpoint media, posters, interactive games “Cheerful Snakes and Ladders,” and a session of taking blood supplement tablets together. Pre-tests and post-tests were conducted to evaluate respondents' understanding and attitudes before and after education. The results showed low scores during the pre-test. The educational activities conducted affected the schoolgirls' understanding of the effect of anemia on stunting. The post-test results showed a significant increase in participants' knowledge, although there was no significant change in attitude and behavior. This education is expected to contribute to breaking the cycle of stunting through improving the health of the younger generation. The sustainability of this program is expected to be monitored through collaboration with Puskesmas Ciledug, installation of educational posters, filling in the blood supplement tablets schedule calendar, and monitoring of blood supplement tablets consumption.